Escape north! : the story of Harriet Tubman - Kulling, Monica; Flavin, Teresa (New York : Random House, 2003)
Surveys the life of Harriet Tubman, including her childhood in slavery and her later work in helping other slaves escape north to freedom through the Underground Railroad.
Originally published: New York : Random House, c2000, in series: Step into reading. A step 3 book.
Keywords: Tubman, Harriet, -- 1820?-1913 -- Juvenile literature; Slaves -- United States -- Biography -- Juvenile literature; African American women -- Biography -- Juvenile literature; African Americans -- Biography -- Juvenile literature; Underground railroad -- Juvenile literature; Tubman, Harriet, -- 1820?-1913.; Slaves; African Americans -- Biography; Women -- Biography; Underground railroad